STRATEGI MANAJERIAL DALAM MENJAGA DAYA SAING INDUSTRI BATIK INDONESIA DI ERA GLOBALISASI - Simbolon, Mangantar; Remus Silalahi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Globalization has significantly changed the competitive dynamics of the Indonesian batik industry, presenting both opportunities and challenges. This study aims to analyze the managerial strategies implemented to maintain and enhance the competitiveness of the batik industry in the era of globalization. A qualitative approach with a literature review of relevant scientific sources was employed. The findings reveal that globalization intensifies competition, particularly due to the influx of mass-produced batik-patterned textile products from abroad. In response, batik industry players need to adopt integrated managerial strategies, including product innovation based on local wisdom, the use of digital technology in marketing, human resource competency development through training, and the optimization of the marketing mix. The implementation of these strategies has been shown to positively impact business performance, market expansion, and the long-term sustainability of the batik industry. The study implies that an adaptive and holistic managerial approach is essential to navigating the complexities of global competition.